THE CONSISTENCY OF TEXTBOOK â€œPATHWAY TO ENGLISH FOR SMA/MA GRADE Xâ€ WITH THE 2013 CURRICULUM - Laili, Noor; Wahyanti, C. Murni (ELT Forum: Journal of English Language Teaching, 2018)
The aim of the study is to analyze whether the textbook â€œPathway to English for SMA/MA Grade Xâ€ publisehd by Erlangga pass the BSNP assessment and the content is consistent with the 2013 Curriculum. This study used qualitative content consistency analysis as its research method. The data were collected from the English textbook â€œPathway to English for SMA/MA Grade Xâ€ written by Th. M. Sudarwati et al., published by Erlangga in 2016. The data analysis used two instruments: the assessment based on KI-KD of the English syllabus of 2013 Curriculum and the rubric assessment by BSNP textbook evaluation. The discussion was focused on the content consistency of the materials in the textbook. There are two main findings. First, by using KI 3-4 and KD of the syllabus 2013 Curriculum the percentage obtained is 94% (very good). Based on the assessment, it is discovered that all the materials in the textbook are consistent with the KI 3-4 and the KD of the syllabus 2013 Curriculum. Second, by using BSNP assessment the percentage obtained is 81.25% (very good). Based on BSNP assessment, it revealed that all the materials in the whole chapters of the textbook are consistent with the criteria of the 2013 curriculum.